Ustadz Abdul Somad's Da'wah message on Youtube Meanings and Media Perspective - Hafniati Abdul Hadi (Wardah, 2022)
Ustadz Abdul Somad is one of the preachers who uses social media (youtube) in delivering his da'wah. Da'i as a sign. Da'wah message as a marker. Ustadz Abdul Somad as a marker. Ustadz Abdul Somad appeared in a koko shirt and a cap. He lectured with easy-to-reach and humorous language and rhetoric. Ustadz Abdul Somad delivered his da'wah using words, signs and symbols on YouTube. He uses sentence structures with a distinctive style. Language style based on structure with a Malay accent. The material presented contains a deep meaning that can be reached by denotation and connotation. The theory used is meaning and media, namely the theory of meaning which explains in detail and detail an object with semiotic analysis, structuralism, as well as denotation and connotation. Semiotics is the study of signs in human social life, influenced by the system (or law) that applies in it. Structuralism is a semiotic explanation of the insistence that signs are fully understood only by reference to differences from other signs in a particular system or code of representation. Denotation is the actual meaning, or a phenomenon that appears with the five senses, or it can also be called a basic description. Connotations are cultural meanings that arise or can also be called meanings that arise due to cultural construction so that there is a shift, but remains attached to the symbol or sign.